1992
DOI: 10.1002/cne.903200103
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of meningeal cells over the medial cerebral hemisphere of newborn hamsters prevents the formation of the infrapyramidal blade of the dentate gyrus

Abstract: Meningeal cells participate in the development of the cerebellum both by stabilizing the extracellular matrix of the pial surface and by organizing the radial glial scaffold and the lamination of the cerebellar cortex. In the present study we investigated possible influences of meningeal cells on the development of the dentate gyrus, whose ontogenesis has many similarities to that of the cerebellum. Meningeal cells were selectively destroyed by injecting newborn hamsters with 25 micrograms 6-hydroxydopamine (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Informatively, the tissues we show to express SDF-1 have been implicated previously in dentate granule cell migration (21). Selective destruction of medial cerebral meningeal cells, with secondary degeneration of the Cajal-Retzius cells lining the hippocampal fissure, leads to a defect in DG morphogenesis, apparently via a disruption of granule cell migration (21,28). Our present findings indicate that the loss of SDF-1͞ CXCR4 signaling could, at least in part, mediate this migratory defect.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Informatively, the tissues we show to express SDF-1 have been implicated previously in dentate granule cell migration (21). Selective destruction of medial cerebral meningeal cells, with secondary degeneration of the Cajal-Retzius cells lining the hippocampal fissure, leads to a defect in DG morphogenesis, apparently via a disruption of granule cell migration (21,28). Our present findings indicate that the loss of SDF-1͞ CXCR4 signaling could, at least in part, mediate this migratory defect.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, we analyzed expression of CXCR4 and SDF-1 in CD-1 mice at 6-10 weeks of age. Late dentate granule neurons arise from dividing cells in the DG hilus or along the inner surfaces of the DG blades (25,28). In the adult, we found that SDF-1 now is expressed strikingly in the DG blades (Fig.…”
Section: Dgmentioning
confidence: 64%
“…Historically, no distinctions in the functional, structural, and neural innervation of the two blades of the dentate gyrus have been emphasized. However, more recent studies have identified a number of neurochemical, neuroanatomical, and functional differences between the two blades (Hartmann et al 1992;Tamamaki 1997;Scharfman et al 2002;Choi et al 2003;Kim et al 2004;Witter and Amaral 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, CXCR4 is expressed in the germinal region of the rhombic lip, the only region from which the cerebellar granule cell precursors are generated (Wingate RJ and Hatten ME, 1999;Tissir F et al, 2004). Previous studies demonstrated that selective destruction of the meninges in this region causes reduction of the superficial basal lamina, a misrouting of cell migration within the VZ and the abnormal development of radial glia (Hartmann D et al, 1992;Sievers J et al, 1994;Hartmann et al, 1998).…”
Section: Cerebellar Granule Precursor Cells-mentioning
confidence: 98%